Immersive Versus Non-immersive Experience: Exploring the Feasibility of Memory Assessment Through 360° Technology - Ventura, Sara; Brivio, Eleonora; Riva, Giuseppe; Baños, Rosa M. (Frontiers in Psychology, 2019)
Episodic memory is essential to effectively perform numerous everyday life activities and it enables individuals to consciously recall experiences along with their spatial and temporal environments. Virtual Reality (VR) serves as an efficacious instrument to assess cognitive functions, such as attention and memory. Previous works have adopted VR computer simulated to assess memory revealing high benefits when compared to traditional procedures (paper and pencil). One of the most recent trends of immersive VR experience is the 360 technology. In order to evaluate its potentiality, the present paper aims to compare memory performance in two tasks: immersive task and non-immersive task. In detail, we aim to investigate if a 360 immersive picture could facilitate memory ability in comparison to a non-immersive 360 picture. A repeated measure design was carried out in a sample of 42 participants, randomized into two groups, 21 for each: Group 1 looked first at picture A (immersive) and then at picture B (non-immersive) and Group 2 looked first at picture B (non-immersive) and then at picture A (immersive). The two 360° pictures contain specific items and some items are shared by each one. Memory evaluation was assessed immediately after the exposure (recall task) and after a 10-minute delay (recognition task). Results revealed that immersive set-up strengthens memory performance in the long-term task compared to the non-immersive condition. Overall, the data provides preliminary evidence in support of 360 technology to evaluate executive function.